Understanding rural household behavior: Beyond boserup and becker - Doss, Cheryl R.; Quisumbing, Agnes R. (International Association of Agricultural Economists, 2020)
New data and new methods have provided many new insights into rural households in the past 50 years. We analyze what we have learned from household models since Boserup and Becker, using this to frame more recent findings about household behavior from three types of studies: observational studies, experimental games, and impact evaluations. More sex‐disaggregated data as well as data that is collected at smaller units, such as agricultural plots, has allowed us to better understand agricultural productivity, risk sharing, and spousal cooperation. However, the focus on bargaining within households has often led us to ignore the cooperation that occurs within households. Many resources are owned and managed jointly by household members and many decisions are made jointly, although not all parties necessarily have equal voice in these decisions. Research demonstrating that households often do not reach efficient outcomes suggests that we still have much to learn about rural household behavior. Understanding both individual roles within households and the levels of cooperation, including joint decision‐making and ownership of resources, is essential to analysis of households, especially in rural areas where households engage in both production and consumption.